Service Quality Analysis with Servqual Integration Approach and Importance Performance Analysis (IPA) to Increase Customer Satisfaction at Radja Mart Minimarket - Desi Sri Setiawati; Supriyati Supriyati; Rachman Catur Kurniawan (G-Tech: Jurnal Teknologi Terapan, 2025)
Radja Mart minimarket faces the problem of mismatch between customer expectations and the quality of service provided. This study aims to measure the level of customer satisfaction with Radja Mart's services, analyze factors that affect service quality with the Servqual and Importance Performance Analysis (IPA) methods, and determine the priorities for improvements that need to be made. The study findings indicate that Radja Mart's service quality does not yet fully meet customer expectations, as evidenced by an average Servqual score of 0.94 <1, which means that there is still a lack of service quality provided by Radja Mart. The Cartesian chart analysis identified the E3 attribute response to customer complaints and suggestions identified as the top priority for enhancement. To improve service quality, Radja Mart should implement concrete measures such as regular employee training to enhance responsiveness and customer engagement. Furthermore, establishing a structured feedback mechanism will enable management to monitor customer concerns and promptly address service gaps. By focusing on these targeted improvements, Radja Mart can increase customer satisfaction, minimize complaints, and strengthen its market competitiveness.